Climate change and dengue Fever: A 14-year study of mortality trends during 2010–2023 in Indonesia - Kurnia Ardiansyah Akbar; Rosa Kumala Fatma; Fauzi Elamouri; Jürgen Kurt Rockstroh (Travel Medicine and Infectious Disease)
Background: Dengue fever remains a critical public health issue in Indonesia, with a significant increase in mortality cases in recent years. As a vector-borne disease, dengue fever is highly influenced by environmental conditions, making it particularly sensitive to the impacts of climate change. Indonesia, being heavily affected by global climate change, faces increasing challenges in managing dengue fever. This study aims to investigate the association between dengue fever mortality and climate variables, specifically annual rainfall, and temperature, in Indonesia from 2010 to 2023. Methods: Secondary data on dengue fever cases from 2010 to 2023 were collected from the Ministry of Health of Indonesia. Data on annual rainfall and annual temperature were obtained from the Indonesia Meteorology, Climatology, and Geophysics Council, with information gathered from 116 stations across Indonesia. Linear regression analysis was used to determine the association between these variables and dengue fever mortality. Results: The analysis revealed a significant association between annual temperature (p = 0.049; R2 = 0.212; 95 % CI: 710.85–2.233) and dengue fever mortality. Additionally, annual dengue fever cases were significantly associated with mortality (p < 0.001; R2 = 1.075; 95 % CI: 0.007–0.010). However, annual rainfall was not found to be significant in this study. Conclusion: These findings underscore the importance of monitoring climatic changes and their impact on public health, particularly concerning vector-borne diseases. Enhanced surveillance and targeted interventions could mitigate the adverse effects of these climatic variables on dengue fever mortality in Indonesia.